Hasil Belajar Matematika Materi Bidang Datar Menggunakan Media Pembelajaran Cabri II D - Purni Munah Hartuti; Rini Widia Putri Z (SAP (Susunan Artikel Pendidikan), 2020)
The importance of innovations in learning is one of the keys to improving student mathematic’s learning outcome. One of the innovations in learning mathematics is to use Cabri II D for plane geometry. Cabri II D is an interactive software for learning geometry to construct a drawing, like a ruler, calipers, and protractor so that the results can be more accurate. The research objective was to determine the differences in learning outcome of mathematic’s plane geometry using Cabri II D learning media and conventional media. The research method used experimental methods. This research was conducted at SMP PGRI 1 Cibinong with a sample of class 7 consisting of 40 students as the experimental group and class 7.1 consisting of 40 students as the control group. In the experimental class, learning plane geometry was using Cabri II D media, in the control class, learning plane geometry was using ruler, calipers, and protractor. At the end of the topic, a final mathematical test of plane geometry was given in each class. The results showed that there were differences in the average student learning outcome between the experimental group and the control group. The final score of students using Cabri II D learning media was higher than students who used conventional learning media.